ROKOK DAN ALERGI BERHUBUNGAN DENGAN BRONKITIS AKUT PADA PASIEN DEWASA - Gisella Annisa; Rita Khairani (Fakultas Kedokteran Universitas Trisakti, 2024)
Bronchitis refers to a symptom in which the bronchi become inflamed or swollen. Worldwide, the prevalence of chronic bronchitis is estimated to be 3 to 7% in healthy adults. Bronchitis is caused by prolonged exposure to harmful particles or gases and exposure to cigarette smoke. Besides smoking, allergy is also one of the risk factors for bronchitis. Allergies are caused by allergens that can cause inflammation and irritation of the airways. This study aims to determine the relationship between smoking and allergy with the incidence of acute bronchitis at the age of 20-40 years. The research method was observational analytic with a cross-sectional approach involving 76 patients with confirmed acute bronchitis. Data utilized include both primary and secondary sources, with validated questionnaires used to assess smoking habit, allergy, and severity of acute bronchitis. Data analysis employs the chi-square test with a significance set at < 0.05. The prevalence of mild smoking is 63.2% allergy is 50%, and moderate acute bronchitis is 30.3% There is a significant relationship between smoking (p= 0.006) and allergy (p=0.010) and the incidence of acute bronchitis